2012
DOI: 10.1128/jb.06071-11
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bacteriocin Production and Cell Death by the VicRK Signaling System in Streptococcus mutans

Abstract: The VicRK two-component signaling system modulates biofilm formation, genetic competence, and stress tolerance in Streptococcus mutans. We show here that the VicRK modulates bacteriocin production and cell viability, in part by direct modulation of competence-stimulating peptide (CSP) production in S. mutans. Global transcriptome and real-time transcriptional analysis of the VicK-deficient mutant (SmuvicK) revealed significant modulation of several bacteriocin-related loci, including nlmAB, nlmC, and nlmD (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 61 publications
3
87
0
Order By: Relevance
“…Global transcriptome analysis performed by Senadheera and colleagues showed that the SMU.984 gene was regulated by the two-component system VicRK (D. Senadheera, personal communication). In S. mutans, the VicRK system modulates stress tolerance by direct modulation of the CSP pheromone (53). Altogether, these results suggest that SMU.984 could be involved in stress tolerance by modulating the CSP-inducible persistence phenotype.…”
Section: Figmentioning
confidence: 58%
“…Global transcriptome analysis performed by Senadheera and colleagues showed that the SMU.984 gene was regulated by the two-component system VicRK (D. Senadheera, personal communication). In S. mutans, the VicRK system modulates stress tolerance by direct modulation of the CSP pheromone (53). Altogether, these results suggest that SMU.984 could be involved in stress tolerance by modulating the CSP-inducible persistence phenotype.…”
Section: Figmentioning
confidence: 58%
“…Many isolates of S. mutans carry the nlmAB, nlmC (cipB), and nlmD genes encoding mutacin IV, V, and VI, respectively (43). The use of gene fusions and real-time PCR showed that nlmAB (data not shown), nlmC (cipB), and nlmD expression was downregulated in cultures supplemented with 1.5% L-arginine.…”
Section: Discussionmentioning
confidence: 99%
“…VicRK plays an important role in modulating cell division, cell-wall biosynthesis and homeostasis, and membrane integrity, as evidenced by the presence of several genes encoding autolysins and other murein hydrolases in the VicR regulons of B. subtilis [112], S. aureus [109], S. pneumoniae [105], S. mutans [107,113], and S. sanguinis [90]. Consistently, atypical long-chain phenotypes are found in v icK isogenic mutants obtained in S. pnemoniae , S. mutans , and S. sanguinis [90,105,106,111].…”
Section: Vicrk Regulons Of Tcss Are Diverse and Species-specificmentioning
confidence: 99%
“…In addition, VicRK Spn regulates pspA [105], which encodes a species-specific surface protein (PspA) involved in complement evasion [128]. In S. mutans , VicR Sm also directly represses genes involved in competence and competence-induced bacteriocin ( comCDE and nlmC ) [113], and copY [117], part of the copYAZ operon required for copper homeostasis and regulation of membrane potential, competence, and biofilm formation [129]. In S. sanguinis , VicRK Ss does not regulate gtfP , a unique gene encoding a glucosyltransferase for the synthesis of soluble glucan [90] but does regulate spxB encoding pyruvate oxidase, required for conversion of pyruvate, inorganic phosphate, and O 2 to H 2 O 2 , CO 2 , and AcP [130].…”
Section: Vicrk Regulons Of Tcss Are Diverse and Species-specificmentioning
confidence: 99%